Effects of a temperature dependent viscosity in surface nonlinear waves propagating in a shallow fluid heated from below - Kraenkel, Roberto André [UNESP]; Kurcbart, S. M. [UNESP]; Pereira, J. G. [UNESP]; Manna, M. A. (Elsevier, 1992)
The effects of a temperature dependent viscosity in surface nonlinear waves propagating in a shallow fluid heated from below are investigated. It is shown that the (2+1)-dimensional Burgers equation may appear as the equation governing the upper free surface perturbations of a Bénard system, even when the viscosity is assumed to depend on temperature. The critical Rayleigh number for the appearance of waves governed by the Kadomtsev-Petviashvili equation, however, will be smaller than R=30, which is the critical number obtained for a constant viscosity. © 1992.